A reforma psiquiátrica como projeto inacabado: por uma crítica da clínica e da política - Guimarães, Raquel Rubim da Rocha (2018)
The present study intends to discuss the implications of Care Conditions on the way of caring in a Psychosocial Attention Center (CAPS) in the city of Fortaleza. The Care Conditions discussed here are inspired by the studies of the philosopher Judith Butler, understanding them as non-static entities, but institutions and reproducible social relations that sustain and apprehend certain lives. This qualitative research has used as a method of analysis and data collection the “Diário de Campo”, which is not limited to data recording, but, it convokes the researcher to get involved with the field through writing, becoming a tool of registration, affectation and interlocution. Extensive systematic notes and recordings of the team meetings (called “Roda de Conversa”) were used during seven weeks. Along the path of research, the methodological changes necessary to the researcher's entry into the practical field are ponted out, redefining the whole initial objective. We sought to guide the analysis under the lens of Critical Social Psychology in the interlocution with different authors of the Psychiatric Reformation with anti-asylum stamp. In this direction, a historical rescue to understanding changes in brazilian mental health care policies since the end of the 1970s has become important, signaling even the technical assistance changes starting in 2015, with the change in “Mental Health, Alcohol and Other Drugs, General Coordination Management”, pointed out by some Mental Health and workers scholars, as a return to asylum practices. Next, the meetings are presented in a sequential manner, with the proposal to make reading and understanding the design of the research easier. From this chapter and the demarcation of some themes, three categories of analysis were drawn and discussed: Reception in Mental Health, Apathy and Sickening of the “CAPS” Worker; and, Conditions of Care. The critiques elaborated were compromised with the proposal of "deinstitutionalization", an important concept for the care transformation movement. Lastly, pertinent considerations are woven so that the Reformation becomes a permanent project to question the actions of care and its intersections with the political-social conditions.